Cd and Pb reduction in cocoa (Theobroma cacao) nib using two organic amendments.: Reducción de Cd y Pb en la almendra de cacao (Theobroma cacao) utilizando dos enmiendas orgánicas - Dávila Zamora, Edilberto Cesar
In Peru, cocoa (Theobroma cacao) cadmium (Cd) and lead (Pb) content may exceed the established limits for international trade and human consumption. Most farmers in the Peruvian jungle generally do not fertilise their cocoa crop parcels with organic amendments (OA). Therefore, the objective of this study was to evaluate the application of compost and poultry manure in the doses of 30, 60 and 90 MT ha-1 in cocoa plantations to reduce Cd and Pb content in the cocoa nib. The study was conducted from February to November 2015, in Huánuco, Peru. The textural class of soil was loose silty clay, so it did not change after 9 months of applying the OA. The application of OA decreased available Cd and Pb content in soil over 75% and 98%, respectively. Likewise, the total content of Cd and Pb in cocoa nib decreased more than 95% and 67%, respectively (P < 0.05). Therefore, the OA could be a good alternative to reduce Cd and Pb in the cocoa nib.